Optimization of Margins and Plan Robustness for Proton Therapy of Hodgkin’s Lymphoma - Hörberger,Filip (2022)
Purpose/Background: Utilizing proton therapy (PT) for treatment of Hodgkin’s lymphoma (HL) has demonstrated favorable features, particularly a reduced dose to organs at risk (OAR) in comparison with photon radiotherapy. However, there is a coherent complexity with PT including its uncertainties, such as range-uncertainties and set-up variations as protons are highly sensitive to tissue density variations within the beam-path. These are mitigated by using beam-specific target-margins, robust-optimization (RO) and motion mitigation techniques such as Deep Inspiration Breath-Hold (DIBH). Currently, a symmetric 7 mm displacement and 4.5% range-uncertainty (7 mm/4.5%) is applied in the RO-process for HL patients. The purpose of this thesis was to evaluate if the margins for HL PT in DIBH could be reduced and still ensure a robust dose to the target volume, simultaneously as the dose to normal tissue and OARs was minimized. Material and Methods: An evaluation of the original treatment plans (TP) and of TPs with smaller margins, based on a retrospective evaluation of weekly verification CTs (vCT) acquired throughout the treatment course, were conducted in this study. Nine patients, diagnosed with HL who received PT treat- ment with DIBH, were included. A geometric and dosimetric analysis of the original TPs, including the total lung volume variation as well as OAR doses and target coverage(CTV D98%), were performed by recal- culating the original TPs on each acquired vCT to determine any deviations from the planning CT (pCT). Thereafter, three new TPs with smaller margins (5 mm/4.5%, 3 mm/4.5%, 5 mm/3.5%) were optimized and evaluated similar to the original TPs, i.e. with respect to target coverage and OAR doses. Results: From the evaluation of the original TPs, both dosimetric and geometric variations throughout treatment were observed, with clinical target volume (CTV) D98% deviations within 1-3 % for most patients as well as an increase and decrease in OAR doses of up to 5 and 1 Gy (RBE) respectively. In addition, relative lung volume deviations of up to 25% were observed. However, for one patient, CTV D98% was as low as 86% with the original TP. For five out of the nine patients, TPs with smaller margins (5 mm/4.5%) would deliver a robust dose to CTV, with CTV D98% ≥ 96%. Two patients only scarcely achieved a robust dose to CTV throughout treatment with smaller margins. The last two patients already had insufficient target coverage with their original TP, which became more critical when applying smaller margins, e.g. CTV D98% dropped from 86% to 70%. With smaller margins OAR doses were lowered by 0.1 - 1 Gy(RBE). Conclusion: TPs with smaller margins, in particular TP 5 mm/4.5%, demonstrated a sufficient robustness to CTV and lower dose to OARs. On the other hand, smaller margins increase the risk for under-dosing CTV if the patients DIBH reproducibility is poor. Ideally, if implementing smaller margins, knowledge about the DIBH reproducibility at an early stage is required, and replanning would be required to a greater extent.